Humanized childbirth: model of care - Mendes, Janaine Borges Ferreira (2022)
This article reports on humanized childbirth in Brazilian women and the role that nursing plays in these procedures, focusing on the reduction of invasive procedures and disrespect for the woman's body and her decisions. Therefore, the objective of this research is to understand the meaning that nurses give to humanized labor. The research was carried out through a literature review. It was found that childbirth went from a natural experience to an interventionist and dangerous process, as in Brazil more than 40% of births are cesarean. And the relevance of health professionals to pay attention to procedures aimed at the woman's role and the provision of education on the rights of women and children are paramount to combat obstetric violence and increase the quality and effectiveness of humanizing assistance.